To convert the equation \( y - 2 = \frac{3}{2}(x + 2) \) into slope-intercept form (which is \( y = mx + b \)), follow these steps:
-
Distribute \(\frac{3}{2}\) on the right side:
\[ y - 2 = \frac{3}{2}x + \frac{3}{2} \cdot 2 \]
This simplifies to:
\[ y - 2 = \frac{3}{2}x + 3 \]
-
Next, solve for \( y \) by adding 2 to both sides:
\[ y = \frac{3}{2}x + 3 + 2 \]
This simplifies to:
\[ y = \frac{3}{2}x + 5 \]
The equation in slope-intercept form is:
\[ y = \frac{3}{2}x + 5 \]
Here, the slope \( m \) is \(\frac{3}{2}\) and the y-intercept \( b \) is \( 5 \).